Optimized multilayer indium‐free electrodes for organic photovoltaics. Issue 2 (9th October 2014) - Gentle, Angus R.; Yambem, Soniya D.; Smith, Geoff B.; Burn, Paul L.; Meredith, Paul
<x xml:space="preserve">Abstract</x> Flexible multilayer electrodes that combine high transparency, high conductivity, and efficient charge extraction have been deposited, characterised and used as the anode in organic solar cells. The anode consists of an AZO/Ag/AZO stack plus a very thin oxide interlayer whose ionization potential is fine‐tuned by manipulating its gap state density to optimise charge transfer with the bulk heterojunction active layer consisting of poly(n‐3‐hexylthiophene‐2, 5‐diyl) and phenyl‐C61‐butyric acid methyl ester (P3HT:BC61BM). The deposition method for the stack was compatible with the low temperatures required for polymer substrates. Optimisation of the electrode stack was achieved by modelling the optical and electrical properties of the device and a power conversion efficiency of 2.9% under AM1.5 illumination compared to 3.0% with an ITO‐only anode and 3.5% for an ITO:PEDOT electrode. Dark I–V reverse bias characteristics indicate very low densities of occupied buffer states close to the HOMO level of the hole conductor, despite observed ionization potential being high enough. Their elimination should raise efficiency to that with ITO:PEDOT. <inline-graphic xlink:href="ark:/27927/pgh3t3q8ztp" content-type="pssa201431469-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Images of the AZO/Ag/AZO flexible electrodes.